The Comparative of Corporate Performance Analysis Between Pre and Post Mergers and Acquisitions Companies in the Indonesia Manufacturing Industries Listed on The Stock Exchange in 2007-2012 - Rosiwarna Anwar; Fenny Chintya Debby (Jurnal Manajemen dan Bisnis Indonesia, 2016)
This study aims to analyze the performance of companies doing mergers and acquisitions that proxies by Return on Capital Employed (ROCE), Return on Equity (ROE), Operating Profit Margin (OPM), NetProfit Margin (NPM), EPS (Earnings PerShare), PER (Price Earning Ratio). This studyuses the sample based on 90 companies in Indonesia manufacturing industries forthe period from 2007 to 2012.Hypothesis testing is done by using the paired t test. We had documented the results of the study findings ofthe performance of the company which showed the distinction between two conditions, pre mergers and acquisitions when compared with post mergers and acquisitions of companies. However, many out of the results are not statistically significant. Keywords: Mergers & Acquisitions; Corporate Performance; Financial Ratios.